The musculoskeletal profile of female adolescent elite water polo players and the factors affecting throwing performance. - Verwey, Lianne (Department of Health and Rehabilitation Sciences, 2025)
Water polo is a popular water-based sport and a physically challenging game. Water polo demands extreme glenohumeral joint ranges of motion while throwing overhead, which is an entire-body movement requiring accuracy and precision. Water polo is unique as it loads the shoulder in four different ways, where players are required to swim explosively, pass and shoot the ball as well as wrestle with opponents and defend attempts at goal. A marked paucity of research exists regarding the factors affecting throwing performance in this vulnerable population. To date, there is also limited evidence on the musculoskeletal profile of female adolescent water polo players and whether it is comparable to that of other overhead athletes. An overview of the literature (Chapter 2) describes the biomechanics of throwing in overhead sports, and the unique features of throwing biomechanics in water polo. Water polo players are required to throw from an unstable base of support and utilise an egg-beater kick which necessitates different kinetic chain contributions. Further, the parameters of throwing performance and the factors influencing it are discussed. While several studies have analysed musculoskeletal predictors of throwing performance in other overhead sports, very little is known about water polo, especially adolescent females. There are some common factors affecting throwing performance amongst overhead athletes, including anthropometric variables such as gender, age, height and body mass index, which all affect throwing speed and/or throwing accuracy. Range of motion of the glenohumeral joint, hip and knee joints as well as the thoracic spine have all been correlated with throwing speed in other overhead sports. Upper limb strength of the glenohumeral rotators, pectoralis minor muscle, wrist flexors, elbow extensors and grip strength have also been associated with throwing speed. Further, medicine ball throws also predicted throwing speed in cricket, handball and tennis. Lower limb strength in the form of hip abduction and abdominal strength as well as lower limb power were also found to influence throwing speed. There are also some unique variables to water polo which include extrinsic factors such as the presence of a goalkeeper, distance from the goalposts and different environmental conditions, which may affect throwing performance. The musculoskeletal profiles of overhead athletes appear to share features, but there are also unique variables seen in the different overhead sports. Water polo players do not appear to follow the typical ‘thrower's paradox' described for baseballers. Instead, they are found to largely preserve their glenohumeral internal rotation range of motion and have lower glenohumeral external to internal 16 rotator strength ratios. Therefore, the musculoskeletal variables found amongst baseballers are unique and cannot be directly extrapolated to other sports, including water polo. The musculoskeletal profile of female adolescent water polo players and the relationship between these variables and throwing performance have not been well described in the literature. Chapter 3 is the research chapter and describes the musculoskeletal profile of female adolescent water polo players and the musculoskeletal contributors to throwing performance in this population. Age group related changes in musculoskeletal variables and side-to-side asymmetries were investigated. There were three steps in the data collection process. Firstly, informed assent/consent and basic demographic information was obtained after participants had been selected for a regional representative team. Participants completed the Kerlan-Jobe Orthopaedic Clinic questionnaire to assess shoulder functionality. Secondly, a battery of musculoskeletal screening tests was conducted. Anthropometry, pain-provocation tests (Hawkins/Kennedy, Empty Can and Full Can), glenohumeral rotational range of motion, upward scapula rotation, scapular and glenohumeral strength measurements, pectoralis minor length and medicine ball throw tests were included. Finally, participants performed throwing speed and throwing accuracy tests in the pool which were measured with a radar gun and the number of targets hit, respectively. All the collected data was grouped together and analysed using SPSS 28.0 (IBM, Armonk, New York, USA). The condition for statistical significance was set as p